Long range surface plasmon based biosensor for dengue virus detection / Wong Wei Ru - Wong, Wei Ru (2015)
Dengue, a mosquito-borne disease caused by one of the four dengue virus serotypes, is of major public health interest in over 100 tropical and sub-tropical countries worldwide. Dengue infection causes flu-like symptoms and the severe cases can be fatal. Dengue cannot be reliably distinguished in its early stage using existing laboratory diagnostic techniques. In the absence of specific treatment for or vaccine against this disease, an early diagnosis of dengue infection is extremely important to reduce morbidity and mortality. The study in this thesis aimed to develop a compact, cost-effective, label-free, real-time biosensor based on long-range surface plasmon polariton (LRSPP) waveguides for dengue detection. Generally, the LRSPP based biosensor consists of thin gold metal waveguides embedded in CYTOP claddings (a fluoropolymer having a refractive index close to that of biologically compatible fluids) with the incorporation of fluidic channels. Several passive elements such as straight waveguides, S-bends, Y-junctions and couplers were designed for different biosensing applications. The detailed fabrication process of the devices using photolithography technique is described. The sensing performance of straight long-range surface plasmon waveguides was explored theoretically as a function of the metal stripe cross-sectional dimensions and the length of the sensing channel using finite element method (FEM). Three refractive indices of the sensing medium which are slightly below, equal to and slightly above the refractive index of CYTOP were considered. The surface sensitivity and detection limit of the waveguide were evaluated as a function of the adlayer thickness. A trade-off between the insertion loss of the waveguide and the change in insertion loss during sensing was observed. iv Prior to biosensing experiments, the long-range surface plasmon waveguide was characterized optically through cut-back measurements, bulk sensing, and protein sensing experiments. The coupling loss and mode power attenuation obtained from the cut-back measurements agreed very well with the theoretical prediction. The sensing index that matches the refractive index of CYTOP produced the highest output power. The experiment with bovine serum albumin (BSA) demonstrated the ability of the LRSPP waveguide to perform (bio)chemical sensing. Besides, the stability of the experimental setup over time was measured in order to establish a stable baseline for subsequent biosensing experiments. Dengue detection using LRSPP based biosensor was performed using two approaches: direct virus detection (detection of dengue virus antigen) and serological detection (identification of dengue-specific antibodies). The results obtained via serological diagnosis exhibit almost 2-fold higher P/N ratios compared to those collected by conventional immunoglobulin M antibody capture enzyme linked immunosorbent assay (MAC-ELISA). The antigen-based diagnosis also showed comparable results as the conventional method. The detection limit of the biosensor was estimated as ∼ 22 pg/mm2. In addition, the reuse of the biosensors was demonstrated by regenerating the sensing surface down to the virus (or antibody) level or down to the bare gold. In conclusion, the LRSPP based biosensor exhibits potential as the next-generation dengue diagnostic tool at point of care. The sensitivity of the biosensor can be further improved by using phase-dependent structures such as Mach-Zehnder interferometers and Young’s interferometers.